Comparative study of biological activities and multicomponent pattern of two wild Turkish species: Asphodeline anatolica and Potentilla speciosa. (1st November 2016) - Zengin, Gokhan; Menghini, Luigi; Malatesta, Luciano; De Luca, Elisa; Bellagamba, Giuseppe; Uysal, Sengul; Aktumsek, Abdurrahman; Locatelli, Marcello
Abstract: The multicomponent pattern and biological characterization of plant material are essential for pharmaceutical field, in the food supplements quality control procedures and to all plant-based products. These nutrients often show valuable effects related to their consumption due to the occurrence of secondary metabolites that show useful properties on health. In this framework, researches performed on this topic play a central role for human health and drug development process. The aim of this study was to compare phenolics and free anthraquinones multicomponent pattern of two wild Turkish species: Asphodeline anatolica and Potentilla speciosa using validated high-performance liquid chromatography–photogiode array (HPLC–PDA) assays, coupled to biological evaluation. Even if some variances related to biological and enzymatic inhibition activities can be ascribed to other phytochemicals, the reported data support traditional use of Asphodeline anatolica and Potentilla speciosa roots as valuable natural font for the development of novel natural-derived drug formulations and/or food supplements with health and nutritional benefits.